CHEMICAL COMPOSITION OF WHITE MUSTARD (SINAPIS ALBA Z) AT DIFFERENT SOWING TERMS - Yu. N. Sinikh; Kh. Kh. Khairulin (Зерновое хозяйство России)
For the first time on the sod-podzolic, floodplain soils of the Moscow region we studied effects of sowing terms of white mustard (spring, summer, autumn) on green fodder, content of nutrients (nitrogen, phosphorus, potassium) in aboveground and underground parts of plants, productivity of green mass. Besides, we studied effect of the planting depth of green fodder (8-10, 20-22, 25-27 cm) on water-physical, agrochemical figures of soil and on productivity of spring wheat Zlata. We found out that a spring period of white mustard sowing is more preferable and advantageous than a summer one when nitrogen increased on 65, phosphorus on 34 and potassium on 70%. An autumn period of sowing increased nitrogen content in underground parts of the plant, but the content of phosphorus and potassium were less than in a spring period. Productivity of green mass increased on 16% as well. At the planting depth of green fodder 8-10 cm the density of the soil without fertilizers reduced from 1,46 to 0,90 g/cm3 (e.i. 38%). Ultimately, the productivity of spring wheat Zlata increased on 6,1 c/ha (e.i. 16,6%) at the planting depth 8-10 cm of green manure (siderate) compared with a deep planting.